Academic performance of students in an accelerated medical pathway - Fei Chen; Katherine A. Jordan; Winston Li; Yee Lam; Luigi Pascarella; Catherine L. Coe (Medical Education Online)
Accelerated medical school curricula, such as three-year programs, have gained attention in recent years but studies evaluating their impact are still scarce. This study examines the Fully Integrated Readiness for Service Training (FIRST) program, a three-year accelerated pathway, to assess its impact on students’ academic performance preparedness for residency. In this observational study, we compared the academic outcomes of FIRST program students to traditional four-year curriculum students from 2018 to 2023. We analyzed multiple metrics, including exam performance (United States Medical Licensing Examination Step scores, shelf exam scores, and pre-clinical course scores) and clinical performance scores during the application and individualization phases. Analysis of Variance was used to examine the effect of accelerated pathway program experience relative to traditional 4-year medical school curriculum on the learning outcomes. FIRST program students were on average 1.5 years younger upon graduation than their traditional peers. While FIRST program students scored slightly lower on Step 2 Clinical Knowledge (CK), they exhibited no significant differences in other exam scores or clinical performance relative to the traditional students. Notably, FIRST students achieved equivalent clinical performance ratings during critical clerkships and rotations. Our findings suggest that a three-year medical school curriculum can effectively prepare students for residency and produce graduates with comparable medical knowledge and clinical skills, offering potential benefits in terms of financial relief and personal well-being for medical students.